Solution design for low-fluorine trifluoroacetate route to YBa2Cu3O7 films. (16th December 2015) - Palmer, X; Pop, C; Eloussifi, H; Villarejo, B; Roura, P; Farjas, J; Calleja, A; Palau, A; Obradors, X; Puig, T; Ricart, S
Abstract: We present our work in the preparation of metallorganic precursor solutions with reduced fluorine content, able to fulfil the requirements for high-performance superconducting YBCO epitaxial layers as a promising approach to low cost and scalable coated conductors. Six different solutions using different quantities of fluorine and non-fluorine carboxylate precursors with a total amount of fluorine from 10 to 50% that of standard trifluoroacetic acid (TFA) solutions. For stabilization purposes different coordinating agents have been used and the solution rheology has been modified for proper substrate wettability. Thermal decomposition analysis and infrared spectroscopy performed directly in films, have revealed that the decomposition takes place in two consecutive stages around 265 and 310 °C respectively, and nuclear magnetic resonance (NMR) analysis could unveil the chemical reactions taking place in the solution. Using the solutions with 20% fluorine and upon optimization of the growth process parameters, YBCO layers with T c and J c (77 K) of 90 K and 4 MA cm −2 are obtained.